2020
DOI: 10.1002/cctc.202000195
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation with Cu/ZnO/Al2O3: A Benchmark Study

Abstract: The suitability of a commercial and industrially applied Cu‐based catalyst for the synthesis of methanol by CO2 hydrogenation was investigated. Unexpectedly, this system showed high stability and well‐performance under conditions that may be relevant for chemical energy conversion using hydrogen and energy from renewable technologies. This Cu‐based catalyst demonstrated excellent suitability for dynamical process operation that may be essential for effective compensation of the volatility of renewable energy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…• C and 50 bar, the productivities are generally higher for the CO 2 -rich feed composition compared to the CO-rich composition (Table 4), which agrees with results reported in the literature [70][71][72][73][74]. In preliminary experiments, we observed a decrease in productivity using CO 2 -rich feed at reaction temperatures ≥250 • C. In this context, we refer to Ruland et al [70], who studied CO 2 hydrogenation using a commercial CZA catalyst and reported a decrease in the conversion of CO 2 -rich syngas with increasing temperature. A detailed kinetic investigation goes beyond the scope of this work and is focus of an upcoming study.…”
Section: Evaluation Of the Catalytic Activity And Correlation With Masupporting
confidence: 91%
“…• C and 50 bar, the productivities are generally higher for the CO 2 -rich feed composition compared to the CO-rich composition (Table 4), which agrees with results reported in the literature [70][71][72][73][74]. In preliminary experiments, we observed a decrease in productivity using CO 2 -rich feed at reaction temperatures ≥250 • C. In this context, we refer to Ruland et al [70], who studied CO 2 hydrogenation using a commercial CZA catalyst and reported a decrease in the conversion of CO 2 -rich syngas with increasing temperature. A detailed kinetic investigation goes beyond the scope of this work and is focus of an upcoming study.…”
Section: Evaluation Of the Catalytic Activity And Correlation With Masupporting
confidence: 91%
“…This effect is shown in both our own experiments and experiments from literature. 51 Still, the model adequately simulates this region (low temperature and high ȳ CO 2 ,0 ) for lower values of GHSV is lower (which means higher conversion). This is demonstrated in the simulation of the experiments from Slotboom et al 16 which have no CO in feed (ȳ CO 2 ,0 = 1) and are reasonably reproduced.…”
Section: Forward Reactionmentioning
confidence: 92%
“…The corresponding flow charts and the further experimental procedure for the investigations on the impact of impurities on the industrial Cu/ZnO/Al 2 O 3 catalyst are described in detail in the Supporting Information (SI). Further information on the catalyst used in this study can be found in a previous publication [28]. To ensure the comparability of the results obtained with different setups applied in the Carbon2Chem project, a standardized benchmark test was performed.…”
Section: Methodsmentioning
confidence: 99%